Resonance in vocal techniques analysis - Kittimathaveenan, Kajornsak; Thumwarin, Pitak; Pakalong, Nattaporn; Nundrakwang, Songmoung (My University, 2018)
Singers, especially when they start training, tend to have many questions concerning how to control their body as a musical instrument in order to create the sound they want. The fact that we humans can speak since birth does not mean that everyone can also control their vocal tract to make satisfactory singing sounds. Indeed, some people do not fully understand which organs are involved in the production of human speaking and singing sounds. To effectively teach singers, it is necessary to encourage them to observe the relationship between the voice organ and the sound they hear. This helps them understand which organs produce their singing voice as opposed to everyday speaking sounds. In this study, signal processing principles were used to analyze singing voices with the aim of helping singers and teachers to easily understand the principles of voice production, and with a focus on the effect of singing with nasal resonance. To fulfill this study, singing sounds were recorded and then processed to display the sound spectrum (amplitude of sound at different frequencies). In addition, the relationship between the voice production and the associated sounds were graphically analyzed.
Keywords: Fourier analysis; music processing; singing voice; speech science; vocal tract; voice acoustics; voice analysis